Tap Crawl From Down Under. Issue 12 (1st December 2016) - Goetz, Melanie K.; Prevos, Peter
Abstract : Employees of a water utility in Australia took time to stand in their customers' shoes by participating in a taste test; the results revealed more than different aspects of the utility's 19 tap waters.